Μελετώντας τη Σχέση Αποδοχής και Κατανόησης της Θεωρίας της Εξέλιξης μέσω Φυσικής Επιλογής σε σχέση με τη Γνώση της Φύσης της Επιστήμης: Η Περίπτωση των Ελλήνων εκπαιδευτικών. - Antonatou, Charis Marina; Evangelia Mavrikaki; Athanasiou, Kyriacos (Μελετώντας τη Σχέση Αποδοχής και Κατανόησης της Θεωρίας της Εξέλιξης μέσω Φυσικής Επιλογής σε σχέση με τη Γνώση της Φύσης της Επιστήμης: Η Περίπτωση των Ελλήνων εκπαιδευτικών., 2024)
The present study aims to investigate questions related, on one hand, to the degree of familiarity that SecondaryScience Education teachers show with the Nature of Science and, on the other hand, to their understanding ofthe Theory of Evolution through Natural Selection. To what extent, e.g. better Epistemological Adequacy(knowledge of the Nature of Science) can influence the understanding and acceptance of the Evolution Theorythrough Natural Selection. Employing a closed-ended electronic questionnaire, the epistemologicalperceptions, understanding, and knowledge of the Evolution Theory via natural selection were assessed amonga cohort of 200 secondary education educators who teach or have taught biology-related subjects. The analysisreveals a positive correlation between epistemological adequacy and the acceptance and understanding ofevolutionary theory via natural selection. (12) (PDF) Μελετώντας τη Σχέση Αποδοχής και Κατανόησης της Θεωρίας της Εξέλιξης μέσω Φυσικής Επιλογής σε σχέση με τη Γνώση της Φύσης της Επιστήμης: Η Περίπτωση των Ελλήνων εκπαιδευτικών. Περίληψη. Available from: <a href="https://www.researchgate.net/publication/381341712_Meletontas_te_Schese_Apodoches_kai_Katanoeses_tes_Theorias_tes_Exelixes_meso_Physikes_Epiloges_se_schese_me_te_Gnose_tes_Physes_tes_Epistemes_E_Periptose_ton_Ellenon_ekpaideutikon_Perilepse?channel=doi&linkId=6669d54185a4ee7261bf2034&showFulltext=true#fullTextFileContent">https://www.researchgate.net/publication/381341712_Meletontas_te_Schese_Apodoches_kai_Katanoeses_tes_Theorias_tes_Exelixes_meso_Physikes_Epiloges_se_schese_me_te_Gnose_tes_Physes_tes_Epistemes_E_Periptose_ton_Ellenon_ekpaideutikon_Perilepse?channel=doi&linkId=6669d54185a4ee7261bf2034&showFulltext=true#fullTextFileContent [accessed Jun 12 2024].